2016
DOI: 10.1111/ijfs.13270
|View full text |Cite
|
Sign up to set email alerts
|

Mucilage formation in food: a review on the example of okra

Abstract: Summary Formation of a mucilage is a complex process that involves the initial contact of a solid matrix (e.g. bone with connective tissue, okra fruit, beans) and water; the wetting of the macromolecules that are embedded on the solid matrix, followed by its swelling; their elution (‘extraction’) in the aqueous phase, forming a hydrocolloidal dispersion; the relaxation of the macromolecules in their new environment, leading to the modification of the latter's rheological properties, or their adsorption onto an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…This behavior would be favored by the presence of long side chains, their arrangement in space under the effect of electrostatic repulsion, and the degree to which they entangle with each other to form a more or less flexible structure. In the case of okra suspensions, this explanation is plausible since it has been shown that okra pectins are of variable length and branching, with more or less long side chains (Kpodo et al, ) and that they can entangle with each other via hydrogen, hydrophobic, and calcium bonds (Ritzoulis, ). In fact, the samples (no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior would be favored by the presence of long side chains, their arrangement in space under the effect of electrostatic repulsion, and the degree to which they entangle with each other to form a more or less flexible structure. In the case of okra suspensions, this explanation is plausible since it has been shown that okra pectins are of variable length and branching, with more or less long side chains (Kpodo et al, ) and that they can entangle with each other via hydrogen, hydrophobic, and calcium bonds (Ritzoulis, ). In fact, the samples (no.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their sliminess, they have original thickening, shear thinning, viscoelastic and visco‐elastic properties (Kontogiorgos, Margelou, Georgiadis, & Ritzoulis, ; Ndjouenkeu et al, ; Sengkhamparn et al, ), emulsifying properties (Kpodo et al, ), and elongational properties (Yuan, Ritzoulis, & Chen, ) properties. The rheological properties of okra mucilage are the result of complex interactions between the various macromolecular populations of which it is composed (Ritzoulis, ), including very specific pectic compounds (Kpodo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The zeta potential of OC5 was measured to be −9.3 ± 1.0 mV, while that of OC7 was measured to be −26.8 ± 1.0 mV; the reader should be reminded that all zeta potential measurements were taken at pH 7, using samples extracted at different pH values (OC5, OC7, OC9); so their different zeta potentials reflected real compositional differences. That suggested that entities of higher density in ionizable moieties (e.g., carboxyls) were extracted at pH 7 and pH 9 (as compared to pH 5); this could explain the smaller content of degradation products (or products of lower MW) in OC7 and C9 as compared to OC5: For a molecule to be extracted from a plant matrix, the force between the hydrating water and the molecule under extraction should be larger than the forces acting between that molecule and the plant matrix [14]. At pH 7 or 9, the charges were higher than at pH 5 (as at pH 5, most proteins were closer to their pI).…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations could also be made for the large droplets at pH 7 (lower part micrographs). A rightward shift of the droplet size distribution, coupled with the growing was the size of the larger droplets at the expense of the smaller ones, was indicative of Ostwald ripening, rather than coalescence [14]. This means that a strong mechanical layer, capable of protecting against droplets merging/coalescing, was indeed formed by the novel emulsifiers; in order to control; the stability of these emulsions, one should seek to control parameters which influence Ostwald ripening rather than coalescence, such as the surface elasticity, the solubility of the oil into water, the surface tension and the viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsic viscosity of okra polysaccharides is largely dependent on the extraction protocol, 16,17 hence the structural attributes of the supermolecular structures are dependent on the extraction sequence as well. 18 The extracts from okra are also particular due to their viscoelastic component. 19 Senghamparn et al 20 report that their shear elastic response can be dependent on the polysaccharide acetylation content, hence the inter-macromolecular interactions.…”
Section: Introductionmentioning
confidence: 99%